Taxonomic, molecular and landing status assessment of spiny lobster (panulirus spp.) distribution in the waters of Sabah and Pulau Layang-layang, Malaysia - Ng, Wei-Ling (2023)
In comparison to other crustacean species, spiny lobsters of the family Palinuridae Latreille, 1802 are renowned on the international fishing market. In shallow tropical and subtropical waters (<100 m depth), Panulirus spp. is ubiquitous and abundant, yet knowledge on its range, biodiversity, and population abundance in Malaysia is limited. In addition, there are grave worries regarding the sustainability of their marine harvests due to anthropogenic pressures and climate change impacts on the ocean ecosystem. In the present study, a checklist of Panulirus spp. from the seas of Sabah and Pulau Layang-Layang was compiled using morphological identification and molecular identification utilising the Cytochrome oxidase I (COI) gene. The Department of Fisheries Sabah and the Meteorological Department of Sabah were consulted for information on spiny lobster landings and climate factors throughout a 30-year period (1990-2019). Recent research uncovered seven species: P. ornatus, P. versicolor, P. longipes longipes, P. polyphgus, P. homarus homarus, P. femoristriga (new record), and P. penicillatus (new record). The intra-species p-distance is 6%, validating the respective species, whereas the inter-species p-distance is >10%. Additionally, spiny lobster landings were high throughout the third decade of examined years (2010-2019), but landings were low during the first decade of studied years (1990-1999). Landings of spiny lobster varied significantly between stations (p<0.001). Kudat (849.47 MT) had the largest total landing across the thirty-year study period, followed by Tawau (486.41 MT) and Kota Kinabalu (404.51 MT) (376.48 MT). The yearly landings of spiny lobsters were negatively correlated with both total rainfall and total wet days (r=-0.257, p=0.022; r=-0.253, p=0.024). Kota Kinabalu experienced the highest average rainfall (2,675.90 mm) across the thirty-year study period, resulting in the lowest landings of spiny lobsters. After over 20 years since the last survey in Sabah, the current study represents the most exhaustive record of the existing species of Panulirus spp. This study filled in the missing data of a valuable marine biodiversity group (spiny lobsters) in Malaysia, where the acquisition of biological knowledge is vital to the protection of the world’s natural resources and to the sustainable management of spiny lobster fisheries.